Cisco 802.11 wireless networking quick reference - Velte, Toby J. (Cisco Press, 2006)
This book is part of the Networking Technology Series from Cisco Press®, which offers networking professionals valuable information for constructing efficient networks, understanding new technologies, and building successful careers.